Promising immunotherapeutic approaches for primary effusion lymphoma - Jutatip Panaampon; Seiji Okada (Open Exploration Publishing Inc., 2024)
Primary effusion lymphoma (PEL) is a large B-cell neoplasm usually presenting as a serious effusion in body cavities without detectable tumor masses. It is an AIDS-related non-Hodgkin's lymphoma (HL) with human herpes virus 8 (HHV8)/Kaposi sarcoma-associated herpes virus (KSHV) infection. A combination antiretroviral therapy (cART) prolongs the lifespan of AIDS and AIDS-related malignant lymphoma patients, but PEL continues to have a dismal prognosis. PEL showed disappointing outcomes with standard chemotherapy such as CHOP or CHOP-like regimens. A PEL status highlights the urgent need for new therapeutic approaches and treatment strategies and improve clinical outcomes. This review discusses the current knowledge and some recent clinical trials for PEL in the platform of immunotherapy as well as promising future immunotherapeutic approaches for PEL.